2023
DOI: 10.3389/fmicb.2023.1189859
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the effect of climate change on soil microbial community in an Abies georgei var. smithii forest

Abstract: Qinghai–Tibet Plateau is considered a region vulnerable to the effects of climate change. Studying the effects of climate change on the structure and function of soil microbial communities will provide insight into the carbon cycle under climate change. However, to date, changes in the successional dynamics and stability of microbial communities under the combined effects of climate change (warming or cooling) remain unknown, which limits our ability to predict the consequences of future climate change. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…The underlying mechanism might be related to the changes in temperature between seasons. Temperature changes alter the composition of bacterial communities in the soil (Fu et al, 2023 ). Dedysh and Sinninghe-Damste ( 2018 ) have shown that most Acidobacteria (Koribacteraceae, Acidobacteriaceae, and Solibacteraceae) either are classified as mesophiles or psychrotolerants with slow metabolic activity, that is, low temperature does not inhibit them as other microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism might be related to the changes in temperature between seasons. Temperature changes alter the composition of bacterial communities in the soil (Fu et al, 2023 ). Dedysh and Sinninghe-Damste ( 2018 ) have shown that most Acidobacteria (Koribacteraceae, Acidobacteriaceae, and Solibacteraceae) either are classified as mesophiles or psychrotolerants with slow metabolic activity, that is, low temperature does not inhibit them as other microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, climate warming may increase the rate of enzymatically-catalysed reactions, thereby impacting soil chemical properties (Luis Moreno et al, 2022b). Warming can also cause changes in the structure of fungal and bacterial communities in different soil layers, with more pronounced effects observed with increasing temperatures (Fu et al, 2023). Multifactor climate change, including temperature increases, has an impact on microbial responses, potentially affecting the diversity and function of microbial communities and their enzymes (Steinweg et al, 2013b).…”
Section: The Impact Of Climate Change On Soil Ecosystemmentioning
confidence: 99%
“…This can be explained by the fact that the present study focused on the seedling stage, whereas most previous studies on drought have considered only the maturity stage of wheat. Several studies have shown the influence of different plant development stages on the response of the soil microbial community to different environmental stresses [90][91][92][93]. Therefore, future studies on drought need to consider the different stages of plant development to provide a clearer understanding of this climatic stress on the soil microbial community.…”
Section: Influences Of Various Water Regimes and Fertilization Modes ...mentioning
confidence: 99%